Currency Crises, Capital Account Liberalization, and Selection Bias - Reuven Glick; Xueyan Guo; Michael Hutchison (University of Copenhagen, Economic Policy Research Unit (EPRU), 2004)
Are countries with unregulated capital flows more vulnerable to currency crises? Efforts to answer this question properly must control for self selection bias since countries with liberalized capital accounts may also have more sound economic policies and institutions that make them less likely to experience crises. We employ a matching and propensity score methodology to address this issue in a panel analysis of developing countries. Our results suggest that, after controlling for sample selection bias, countries with liberalized capital accounts experience a lower likelihood of currency crises. That is, when two countries have the same likelihood of allowing free movement of capital (based on historical evidence and a very similar set of identical economic and political characteristics at a point in time)and one country imposes controls and the other does not
Keywords: 330; the country without controls has a lower likelihood of experiencing a currency crisis. This result is at odds with the conventional wisdom and suggests that the benefits of capital market liberalization for external stability are substantial.; Währungskrise; Finanzmarktregulierung; Portfolio-Management; Bias; Entwicklungsländer